2017
DOI: 10.1080/21505594.2017.1342920
|View full text |Cite
|
Sign up to set email alerts
|

Mucorales spores induce a proinflammatory cytokine response in human mononuclear phagocytes and harbor no rodlet hydrophobins

Abstract: Mucormycoses are life-threatening infections in immunocompromised patients. This study characterizes the response of human mononuclear cells to different Mucorales and Ascomycota. PBMC, monocytes, and monocyte derived dendritic cells (moDCs) from healthy donors were stimulated with resting and germinated stages of Mucorales and Ascomycota. Cytokine response and expression of activation markers were studied. Both inactivated germ tubes and resting spores of Rhizopus arrhizus and other human pathogenic Mucorales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…This layer is shed when spores swell and germinate, providing an opportunity for phagocyte detection. There is no evidence of hydrophobins similar to RodA in the mucormycete lineage 73 , however resting and swollen Rhizopus spores demonstrate limited immunogenicity 62 . We hypothesized that masking of the spore surface might allow R. microsporus spores to evade host detection.…”
Section: Resultsmentioning
confidence: 99%
“…This layer is shed when spores swell and germinate, providing an opportunity for phagocyte detection. There is no evidence of hydrophobins similar to RodA in the mucormycete lineage 73 , however resting and swollen Rhizopus spores demonstrate limited immunogenicity 62 . We hypothesized that masking of the spore surface might allow R. microsporus spores to evade host detection.…”
Section: Resultsmentioning
confidence: 99%
“…We have presented a novel interdisciplinary strategy to understanding the interplay between the host immune response and mucormycetes. Recent work has shown that spores induce proinflammatory responses upon encountering macrophages ( 17 , 47 ). Our data suggested that proinflammatory signals are beneficial in controlling mucormycosis by inducing phagocyte recruitment, and both phagocyte number and activity were found to be required for protection from disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…In a model of invasive Mucorales infection, peripheral blood mononuclear cells (PBMCs), monocytes, and monocyte-derived dendritic cells (mDCs) from healthy donors were stimulated with resting and germinated stages of Mucorales and Ascomycota. Both inactivated germ tubes and resting spores of Mucorales species significantly stimulated mRNA synthesis and secretion of proinflammatory cytokines, including IL-6 and TNFα, and induced the upregulation of co-stimulatory molecules on mDCs and a T-helper cell response [57]. Another model of stimulated mononuclear cells examined TNFα and IL-6 secretion to cells exposed to different pathogenic fungi.…”
Section: Anti-mold Immune Response: the Impact Of The Host And The Pamentioning
confidence: 99%